Model Pengorganisasian Sistem Informasi Instalasi Gigi Mulut sebagai Sub Sistem Informasi Rumah Sakit - Winata, Tjen Dravinne; Budiharto, Budiharto; Bachtiar, Adang (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2010)
The focus of this dissertation is about obligation organization processes data at organization, department, and end user level in administration, billing, clinical and non clinical patients management when Indonesian Police Hospital Raden Said Sukanto developing dental instalation information system as part of hospital information system to produce a model. This research use qualitative with case study methodology. As a conclution of this study suggest that Model can be use by hospital to collect organization processes data that can be use to plan or guide dental instalation information system development with better performance and more user satisfaction.